2012
DOI: 10.1007/s13593-012-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Participatory design of agricultural decision support tools: taking account of the use situations

Abstract: Although many agronomic researchers currently focus on designing and developing decision support systems, they rarely discuss the methodological implications of such work. In this paper, with the examples of two decision support systems, we propose methodological elements for conducting the participatory design of such tools. Our proposition aims at building dialogue between designers and users but also between humans, tools and work situations. We focus on two main stages: first, a diagnosis of the uses of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 30 publications
1
64
0
14
Order By: Relevance
“…This supports tool design that fits the intended purpose and end users. Cerf et al (2012) showed significant differences between designers' and users' interpretations of a problem, and experienced so-called "debriefing sessions" between researchers and end users as learning environments for researchers. They stressed the importance of involving end users early in the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports tool design that fits the intended purpose and end users. Cerf et al (2012) showed significant differences between designers' and users' interpretations of a problem, and experienced so-called "debriefing sessions" between researchers and end users as learning environments for researchers. They stressed the importance of involving end users early in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment tools have been developed for various levels of the food production system; i.e., farm, regional, national, or global (Bockstaller et al 2009, Binder et al 2010. Because of the complexity of food production systems, different types of tools have been developed (de Ridder et al 2007, Binder et al 2010, ranging from indicator sets (e.g., Girardin et al 2000, Rigby et al 2001, Zahm et al 2008, Grenz et al 2011) to simulation models (e.g., Cerf et al 2012, Van Meensel et al 2012. These tools make complex sustainability issues more tangible, and therefore support decision-making at the previously mentioned levels (e.g., Halberg et al 2005, Castoldi and Bechini 2010.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the single unifying predictor of success or failure of an AgriDSS, which has been put forth by multiple authors, is the extent to which the end users are involved in the ICT system development process. The necessity of a user-centered design (UCD) approach has been stressed by, e.g., EIP-Agri Focus group report (2015), Cerf et al (2012), Mȃruşter et al (2008a, b), Matthews et al (2008), Thorburn et al (2011), andVan Meensel et al (2012). User-centered design is an approach within the field of human-computer interaction (HCI), aiming to develop and adapt the ICT system based on the users' needs as well as the context of use, rather than forcing the users to change their behavior to accommodate to the ICT system from a top-down perspective (e.g., Benyon 2014;Dix et al 2004;Hartson and Pyla 2012;Preece et al 2002;Rogers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there is an increasing need to design assessment models for the agricultural sector, but no methodological guidelines have been written for using qualitative MCDA software such as DEXi in this design phase. This lack was highlighted by Cerf et al (2012), who show that an increasing number of decision-making models are developed by the agronomic research community, but few studies explain the design of these models.…”
Section: Introductionmentioning
confidence: 99%